Caroxylon (Chenopodiaceae s.str.) in continental southern Africa and Madagascar: a preliminary nomenclatural synopsis and biogeographical considerations - Mucina, Ladislav (Phytotaxa, 2017)
Caroxylon (Chenopodiaceae) has recently been recognised as a separate genus, based on genetic, physiological and morphological data. This paper features a brief history of the taxonomy of Salsola and introduces new nomenclatural combinations in Caroxylon (80 species and one variety) for taxa that were formerly classified within Salsola in southern Africa (including Botswana, Namibia and South Africa) and Madagascar. Caroxylon albidum, C. aphyllum, C. araneosum, C. calluna, C. columnaris, C. divaricatum, C. glabrescens, C. humifusum, C. littoralis, C. salsola, C. tuberculatum and C. zeyheri have been recognised as species of Caroxylon in the region by other authors earlier. C. brevifolium and C. foetidum were excluded from the list of Caroxylon species occurring in southern Africa. Salsola fuliginosa, S. strumulosa, and S. subsericea, all most probably also Caroxylon taxa, remain still to be classified. Caroxylon littorale, C. nigrescens, C. salsola and C. tuberculatum var. flavovirens are lectotypified in this paper. Synonyms, types and distribution data of the taxa are also given, and taxonomic and nomenclatural problems are identified.